MODEL PJBL DENGAN MEDIA LINKTREE UNTUK MENINGKATKAN HUBUNGAN GAYA BELAJAR DENGAN KEMAMPUAN BERPIKIR KRITIS SISWA - Putri, Safina Aulia; Pratiwi, Gita Indah; Sudarti, Sudarti; Rusdhianti Wuryaningrum, Rusdhianti Wuryaningrum (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This study aims to describe the relationship between visual, auditory, andkinesthetic learning styles and students' critical thinking skills, accompanied byLinktree learning media, in grade IV students. This research design usesquantitative research with a correlation approach. Data collection is donethrough a questionnaire and a test. Respondents in this study were 80 grade IVelementary school students at Bangsalsari 5 Jember. Hypothesis testing wascarried out using Spearman's rank correlation analysis and simple linearregression with a significance level of 0.05. The results of the study are asfollows: First, there is a significant relationship between visual learning stylesand critical thinking skills accompanied by Linktree learning media. Second,there is a significant relationship between auditory learning styles and criticalthinking skills accompanied by Linktree learning media. Third, there is arelationship between kinesthetic learning styles and critical thinking skills.Fourth, there is a relationship between visual, auditory, and kinesthetic learningstyles and critical thinking skills accompanied by Linktree learning media. Theresults of the significance test and the correlation coefficient for each learningstyle are as follows: The relationship between visual learning style and criticalthinking skills, with a significance of 0.000, has a correlation coefficient of 0.719.The relationship between auditory learning style and critical thinking skills, witha significance of 0.000, has a correlation coefficient of 0.672. The relationshipbetween kinesthetic learning style and critical thinking skills, with a significanceof 0.000, has a correlation coefficient of 0.686. The relationship between visual,auditory, and kinesthetic learning styles together (simultaneously) and criticalthinking skills with a significance of 0.000 has a correlation coefficient of 0.695.